2021
DOI: 10.3390/rs13112123
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Banana Plants Using Multi-Temporal Multispectral UAV Imagery

Abstract: Unoccupied aerial vehicles (UAVs) have become increasingly commonplace in aiding planning and management decisions in agricultural and horticultural crop production. The ability of UAV-based sensing technologies to provide high spatial (<1 m) and temporal (on-demand) resolution data facilitates monitoring of individual plants over time and can provide essential information about health, yield, and growth in a timely and quantifiable manner. Such applications would be beneficial for cropped banana plants due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Shatangju tree. With the development of UAV technology, UAV images have also been widely used [49][50][51][52][53][54][55][56]. Studies [10][11][12][13] have shown that UAV tilt photogrammetry can quickly and conveniently obtain images and texture information of forests, pine trees, eucalyptus, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Shatangju tree. With the development of UAV technology, UAV images have also been widely used [49][50][51][52][53][54][55][56]. Studies [10][11][12][13] have shown that UAV tilt photogrammetry can quickly and conveniently obtain images and texture information of forests, pine trees, eucalyptus, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Unmanned aerial vehicle (UAV) platforms were used for the measurement of various traits in horticultural crops. For example, UAV-based remote sensing coupled with different machine learning approaches was used for disease detection and classification in potato, tomato, banana, pear, and apple [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ], for tree detection in orchards such as banana and citrus [ 23 , 24 , 25 ], for aboveground biomass estimation in onion, potato, tomato, and strawberry [ 26 , 27 , 28 , 29 ], and other traits of fruits and vegetables [ 23 , 30 , 31 ].…”
Section: High-throughput Phenotyping Platformsmentioning
confidence: 99%
“…Image processing, widely used to solve various agriculture problems such as classification, object detection, object counting, and many more, can help extract crucial information from the image automatically. Canopy height models (CHM) derived from structure from motion or light detection and ranging (LiDAR) technologies represent a technique for canopy height, size, and biomass measurement also used to separate crop pixels from soil [11,12]. Likewise, Otsu thresholding, widely used in many computer vision applications and employable with vegetation indexes, is a single-intensity threshold method that separates pixels into the foreground and background classes [13].…”
Section: Introductionmentioning
confidence: 99%